Contributions of Farm Animals to Immunology - Guzman, Efrain; Montoya, Maria (Frontiers in Veterinary Science, 2018)
By their very nature, great advances in immunology are usually underpinned by experiments carried out in animal models and inbred lines of mice. Also, their corresponding knock-out or knock-in derivatives have been the most commonly used animal systems in immunological studies. With much credit to their usefulness, laboratory mice will never provide all the answers to fully understand immunological processes. Large animal models offer unique biological and experimental advantages that have been and continue to be of great value to the understanding of biological and immunological processes. From the identification of B cells to the realisation that γδ T cells can function as professional antigen presenting cells, farm animals have contributed significantly to a better understanding of immunity.